Place of menstruation in the reproductive lives of women of rural North India - Singh A (Wolters Kluwer Medknow Publications, 2006)
Objective : To ascertain the perceptions and experiences of women regarding menstruation. Methods : An integrated qualitative and quantitative study on reproductive health of Indian women was conducted in two primary health centre areas of rural north India. Present article reports on the perceptions of 1205 women regarding various aspects of menstruation. Results : Major source of information about menarche/menstruation was friends/relatives (72%). Mean age at menarche was ~ 15 years. Very few women (0.4%) used sanitary napkins. Majority of women had strong beliefs about effect of diet on menstruation. Most of them considered menstruation a dirty act and indulged in various taboo behaviours. Initial reaction was of fear/apprehension at menarche in majority of girls. Conclusion: Women in rural north India still hold tranditional beliefs regarding menstruation. Provision of a balanced and healthy family health education package to all girls is recommended.